Mechanical properties and phases evolution in T91 steel during long-term high-temperature exposure. (April 2020) - Li, Yuyang; Du, Jinfeng; Li, Linping; Gao, Kewei; Pang, Xiaolu; Volinsky, Alex A.
Highlights: The paper focused on the evolution of T91 after 130, 000 h in an actual power plant. After 4000 h, V will enter M23 C6 delaying the growth of the M23 C6 -type carbide. After 130, 000 h, the martensite widened, and the Laves phase (Fe2 Mo) formed. With service time increasing, the resist corrosion decreased. Abstract: Scanning and transmission electron microscopy was used to characterize quantity, pattern, size, and distribution of microstructure and precipitated phases in T91 steel exposed to high temperature in the subcritical unit superheater of a specific power plant. The materials were mechanically and electrochemically tested using a universal testing machine and an electrochemical workstation. The structure and performance of the original material and after the long-term service time were compared. The hardness and strength of T91 steel initially increased before they decreased during long-term service. It took 4000 h for the T91 steel to transform from the original to the service state, forming (Cr, Fe, V, Mo)23 C6 multi-component mixed phase, which delayed or inhibited the growth of the M23 C6 -type carbides during the long-term high-temperature service. The MX-type carbide formation would pin dislocations and increase the strength. When the service time was between 4000 and 130, 000 h, the carbide coarsening was obvious, and the effect of solid solution strengthening was reduced, the dislocation density was decreased, reducing the material's strength below the original state level. Electrochemical tests showed that longer service time degraded corrosion resistance of the T91 steel.